Zastosowanie naziemnego skanowania laserowego w inwentaryzacji lasu – przegląd wybranych zagadnień - Krok, Grzegorz; Kraszewski, Bartłomiej; Stereńczak, Krzysztof (Leśne Prace Badawcze, 2020)
Precise determination of forest resources is one of the most important tasks in conducting sustainable forest management. Accurate information about the forest’s resources allows for a better planning of current and future management as well as conservation activities. Such precise information is needed by both, individual forest managers and for developing the national forest policy. In recent years, interest in the use of remote sensing in forest inventory has significantly increased. Remote sensing allows for non-invasive measurements and the automation of data processing. The most accurate source of remote sensing data at the level of the sample plot is terrestrial laser scanning (TLS). Its use in forest inventory has been studied for about two decades. This paper aims to introduce studies on state of the art TLS technology as well as provide an overview of research conducted in stands within the temperate climate zone. This article furthermore discusses issues such as TLS data acquisition, data processing and presents results for the estimation of tree biometric features.